2004
DOI: 10.1152/physrev.00036.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure and Physiological Functions of GABABReceptors

Abstract: GABAB receptors are broadly expressed in the nervous system and have been implicated in a wide variety of neurological and psychiatric disorders. The cloning of the first GABAB receptor cDNAs in 1997 revived interest in these receptors and their potential as therapeutic targets. With the availability of molecular tools, rapid progress was made in our understanding of the GABAB system. This led to the surprising discovery that GABAB receptors need to assemble from distinct subunits to function and provided exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
730
1
10

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 804 publications
(750 citation statements)
references
References 343 publications
9
730
1
10
Order By: Relevance
“…GABA B receptors are expressed extensively in the PAG 124 and are coupled to G i/o subunits, 127 AC is a downstream effector of GABA B receptors. 128 Elevated PKA activity increased GABA currents, causing depolarization and stimulation of GABAergic neurons in the PAG.…”
Section: Molecular Changes In the Periaqueductal Graymentioning
confidence: 99%
“…GABA B receptors are expressed extensively in the PAG 124 and are coupled to G i/o subunits, 127 AC is a downstream effector of GABA B receptors. 128 Elevated PKA activity increased GABA currents, causing depolarization and stimulation of GABAergic neurons in the PAG.…”
Section: Molecular Changes In the Periaqueductal Graymentioning
confidence: 99%
“…Kindling (Asprodini et al, 1992;Poon et al, 2006) and status epilepticus models resulted in a decrease in GABA B R function (Mangan and Lothman, 1996;Chandler et al, 2003;Straessle et al, 2003), which was suggested to contribute to seizure susceptibility. Additionally, GABA B R1 knockout mice developed spontaneous seizures (Bettler et al, 2004), and acute GABA B R blockade increased partial seizure susceptibility in animals (Leung et al, 2005).…”
Section: Reduction Of Ca1 Distal Dendritic Inhibition After Hyperthermentioning
confidence: 99%
“…Two main variants of GABA B1 that differ in their N-terminal domain are generated by alternative promoter usage (Steiger et al, 2004) and give rise to two GABA B receptor subtypes, GABA B1a /GABA B2 and GABA B1b /GABA B2 . They are abundantly expressed in all major brain structures and control excitability of neurons by mediating slow inhibitory neurotransmission (for a review see Bettler et al, 2004).…”
Section: Introductionmentioning
confidence: 99%